Associations between gender, disease features and symptom burden in patients with myeloproliferative neoplasms: an analysis by the MPN QOL International Working Group - Geyer, Holly L.; Bonatz, Karin; Reiter, Andreas (Haematologica, 2017)
The myeloproliferative neoplasms, including polycythemia vera, essential thrombocythemia and myelofibrosis, are distinguished by their debilitating symptom profiles, life-threatening complications and profound impact on quality of life. The role gender plays in the symptomatology of myeloproliferative neoplasms remains under-investigated. In this study we evaluated how gender relates to patients’ characteristics, disease complications and overall symptom expression. A total of 2,006 patients (polycythemia vera=711, essential thrombocythemia=830, myelofibrosis=460, unknown=5) were prospectively evaluated, with patients completing the Myeloproliferative Neoplasm-Symptom Assessment Form and Brief Fatigue Inventory Patient Reported Outcome tools. Information on the individual patients’ characteristics, disease complications and laboratory data was collected. Consistent with known literature, most female patients were more likely to have essential thrombocythemia (48.6% versus 33.0%; P<0.001) and most male patients were more likely to have polycythemia vera (41.8% versus 30.3%; P<0.001). The rate of thrombocytopenia was higher among males than females (13.9% versus 8.2%; P<0.001) and males also had greater red-blood cell transfusion requirements (7.3% versus 4.9%; P=0.02) with shorter mean disease duration (6.4 versus 7.2 years, P=0.03). Despite there being no statistical differences in risk scores, receipt of most therapies or prior complications (hemorrhage, thrombosis), females had more severe and more frequent symptoms for most individual symptoms, along with overall total symptom score (22.8 versus 20.3; P<0.001). Females had particularly high scores for abdominal-related symptoms (abdominal pain/discomfort) and microvascular symptoms (headache, fatigue, insomnia, concentration difficulties, dizziness; all P<0.01). Despite complaining of more severe symptom burden, females had similar quality of life scores to those of males. The results of this study suggest that gender contributes to the heterogeneity of myeloproliferative neoplasms by influencing phenotypic profiles and symptom expression.